Pengembangan Wisata Kampung Heritage Kelurahan Pakelan melalui Video dan Peta Potensi untuk Meningkatkan Branding Wisata - Ansyorie, Mohammad Musthofa Al; Ichwanto, Muhammad Aris; Ariestadi, Dian; Winarno, Agung; Yudhistira, Chrisnanda Iqbal; Novianti, Novianti (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2024)
The city of Kediri has many historical buildings that should be preserved, one of which is located in the Pakelan Village area which was a former Chinatown area in the past. Pakelan Village, Kediri City has tourism potential to be developed with many interesting characteristics such as social life, culture, and several unique buildings, with this uniqueness the tourism potential in Pakelan Village is very large. This potential must be encouraged and developed by the socio-cultural characteristics of the community. The development of sociocultural-based tourism potential through making videos and potential maps is an effort to improve the branding of the tourist area. With service activities from the Malang State University team, they will focus their activities on developing available local wisdom to improve the tourism sector so that it has great competitiveness and is able to become a branding owned by Pakelan Village. In the implementation of tourism branding activities in the Pakelan Village area, involving the Malang State University team who will develop videos and maps of tourism potential. The output of this activity is a final report in the form of the results of the development of the heritage village area of Pakelan Village, Kediri City, and Copyright in the form of videos and maps of tourism potential by carrying out the concept of a sociocultural-based heritage area to improve tourism branding. Kota Kediri memiliki banyak sekali bangunan sejarah yang patut dilestarikan, salah satunya berada di wilayah Kelurahan Pakelan yang merupakan bekas kawasan Pecinan di masa lampau. Kelurahan Pakelan, Kota kediri memiliki potensi wisata untuk dikembangkan dengan banyak karakteristik yang menarik seperti kehidupan sosial, budaya serta beberapa bangunan yang unik, dengan adanya keunikan tersebut potensi pariwisata di Kelurahan Pakelan sangat besar. Potensi ini harus didorong dan dikembangkan sesuai dengan karakteristik sosial budaya masyarakat. Pengembangan potensi wisata berbasis sosioculture melalui pembuatan video dan peta potensi merupakan upaya dalam meningkatkan branding kawasan wisata tesebut. Dengan kegiatan pengabdian dari tim Universitas Negeri Malang akan memfokuskan kegiatannya dengan mengebangkan kearifan lokal yang tersedia untuk meningkatkan sektor pariwisata supaya memiliki daya saing yang besar dan mampu menjadi sebuah branding yang dimiliki oleh Kelurahan Pakelan. Dalam pelaksanaan kegiatan peningkatan branding wisata Kawasan Kelurahan Pakelan, dengan melibatkan tim Universitas Negeri Malang yang akan mengembangkan video dan peta potensi wisata. Luaran dari kegiatan ini adalah laporan akhir yang berupa hasil pengembangan Kawasan kampung heritage Kelurahan Pakelan, Kota kediri dan Hak Cipta beruapa video dan peta potensi wisata dengan mengusung konsep kawasan heritage berbasis socioculture untuk meningkatkan branding wisata.